Children's world atlas - Adams, Simon, 1955-; Atkinson, Mary, 1938-; Phillips, Sarah; Green, David R., 1956- (New York : DK Pub., 2003)
Maps, photographs, illustrations, and text present information about the continents and oceans of the world.
Includes index.
3-6
6.6
Keywords: Atlases